The citrus industry of Tucumán. A proposal of costs and social benefits (Costos y Gestión, 2020)
Several reasons have motivated the author to approach the topic that, opportunely, was proposed as a doctoral thesis: 1. The growing importance and the promising future that, for Tucumán, has the agroindustrial activity of the citriculture. 2. The lack of studies that are oriented to the topic of costs and business management.The citrus industry needs to have models, data and indicators for management control and decision making,that allow to achieve efficiency and reach efficiency, aware of the challenge that faces in the world markets.3. The production derived from the agroindustrial process of the lemon (co-products: concentrated juices, essential oils and dehydrated peel) is exported. Foreign markets are increasingly demanding in quality and prices. The work consists of three chapters. In the first one, the historical antecedents stand out, the importanceof the agroindustrial sector of Tucumán in relation to Argentina and the regional influences in the SouthernHemisphere and in the World. The industrial process is also described, statistical information is collected andprocessed, and indicators are developed. All this forms a proposal to measure the technical performance ofthe productive factors and the determination of the economic productivity of the lemon, which is summarizedin the indicator P.E.L., which combines the corresponding influences of prices, quantities and yields. In thesecond chapter, various models of costs and decisions are developed, which have been addressed by leadingspecialists of academic and professional prestige. In addition, the practical application is carried out in a citruscompany, which the author has chosen and named: MODEL company. In the third chapter, a model of socialcosts and benefits is presented, receiving ideas of welfare economics, which go back to works begun after theyear 1900 by Arthur Pigou, and which were later developed by a whole stream of economists, among others:EF Schumacher, “Small is beautiful”; and Manfred Max Neef (Nobel Economics Economics - 1983), who proposes an economic development on a human scale. Based on this, the author calculates long-term social costsand benefits for the entire citrus industry of Tucumán. The research that he exposes, in the present work,can contribute to achieve a more finished treatment of the problem of environmental pollution and otherexternalities
Keywords: citrus industry; citriculture; agroindustrial process of the lemon; Tucumán; management control; indicator P. E. L; welfare economics.